The Expression of Bcl-2 and BID in Gastric Cancer Cells. (19th February 2014) - Gryko, Mariusz; Pryczynicz, Anna; Zareba, Konrad; Kędra, Bogusław; Kemona, Andrzej; Guzińska-Ustymowicz, Katarzyna
Abstract : Background. Bcl-2 and BID play a major role in the process of apoptosis and their dysfunction underlies carcinogenesis. The study objective was to assess the expression of Bcl-2 and BID in gastric cancer cells in correlation with chosen clinicopathological parameters, presence of Helicobacter pylori infection, and patients' survival. Materials and Methods. The study involved 88 patients operated on for gastric cancer. The expressions of Bcl-2 and BID were determined immunohistochemically. Results. Positive Bcl-2 expression was found in 55.7% and, BID in 53.6% of patients. The Bcl-2 expression correlated with stage pT3 and T4 gastric cancer P < 0.05, with the intestinal type according to Lauren P < 0.001, ulcerated type according to Bormann's classification P < 0.01, and with local lymph node metastases P < 0.05 . Conclusion. The Bcl-2 protein plays a key role in the process of gastric cancer formation and is associated with the growth of definite types of gastric cancer.